1994
DOI: 10.1021/bi00252a001
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chemical Structure of Photoactive Yellow Protein: Novel Thioester-Linked 4-Hydroxycinnamyl Chromophore and Photocycle Chemistry

Abstract: The unique ability of photoactive proteins to capture and use energy from a photon of light depends on the chromophore, its linkage to the protein, and the surrounding protein environment. To understand the molecular mechanisms by which a chromophore and protein interact to undergo a light cycle, we are studying photoactive yellow protein (PYP), a 14-kDa water-soluble photoreceptor from Ectothiorhodospira halophila with a photocycle similar to that of sensory rhodopsin. Here, we report the cloning and sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
358
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(369 citation statements)
references
References 16 publications
(30 reference statements)
9
358
1
1
Order By: Relevance
“…On this basis we initially proposed that the PYP chromophore is bound to the apoprotein via a disulfide bridge. However, subsequent experiments indicated that it is more likely that the chromophore is bound to PYP via a thiol ester (Hoff et al, 1994a;Baca et al, 1994). This point a The calculated exact masses for key ions generated upon positive ion FABMS from the heptapeptide-chromophore conjugate (Figures 2 and 3) are shown together with their measured masses and elemental composition.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…On this basis we initially proposed that the PYP chromophore is bound to the apoprotein via a disulfide bridge. However, subsequent experiments indicated that it is more likely that the chromophore is bound to PYP via a thiol ester (Hoff et al, 1994a;Baca et al, 1994). This point a The calculated exact masses for key ions generated upon positive ion FABMS from the heptapeptide-chromophore conjugate (Figures 2 and 3) are shown together with their measured masses and elemental composition.…”
Section: Resultsmentioning
confidence: 98%
“…However, the exact physical basis of this red shift, i.e., of the spectral tuning of chromophore absorbance by proteins in general, is not well understood. In the case of PYP the protonation state of the phenolic hydroxyl group of the chromophore has been proposed to be important (Baca et al, 1994).…”
mentioning
confidence: 99%
“…PYP belongs to the novel group of photoreceptor proteins (3,4) whose structures are quite different from those of the other photoreceptor proteins studied so far. Namely, the protein moiety of PYP has an ␣/␤ fold structure (5) composed of 125 amino acids (6,7). The chromophore is a p-coumaric acid (7)(8)(9) bound to a cysteine residue via a thioester bond.…”
mentioning
confidence: 99%
“…Namely, the protein moiety of PYP has an ␣/␤ fold structure (5) composed of 125 amino acids (6,7). The chromophore is a p-coumaric acid (7)(8)(9) bound to a cysteine residue via a thioester bond.…”
mentioning
confidence: 99%
“…As an example, the Racker band observed in the NAD + -bound form of E. coli glyceraldehyde-3-phosphate dehydrogenase results from a charge-transfer interaction between Cys159 and the nicotinamide ring (17,18). Many other possible structures could result in an absorption band at 315 nm, including various thioether/thioester cross-links like those found in photoactive yellow protein (19), apo-galactose oxidase (20), and model complexes of apo-galactose oxidase (21). However, because the chromophoric species is destroyed upon alkylation of selenophosphate synthetase, any cysteine cross-link must be reversible such that the nucleophilic thiol(ate) is accessible.…”
Section: Discussionmentioning
confidence: 99%